Evaluation of magnesium‐yttrium alloy as an extraluminal tracheal stent. Issue 3 (2nd May 2013) - Luffy, Sarah A.; Chou, Da‐Tren; Waterman, Jenora; Wearden, Peter D.; Kumta, Prashant N.; Gilbert, Thomas W.
Abstract Tracheomalacia is a relatively rare problem, but can be challenging to treat, particularly in pediatric patients. Due to the presence of mechanically deficient cartilage, the trachea is unable to resist collapse under physiologic pressures of respiration, which can lead to acute death if left untreated. However, if treated, the outcome for patients with congenital tracheomalacia is quite good because the cartilage tends to spontaneously mature over a period of 12 to 18 months. The present study investigated the potential for the use of degradable magnesium‐3% yttrium alloy (W3) to serve as an extraluminal tracheal stent in a canine model. The host response to the scaffold included the formation of a thin, vascularized capsule consisting of collagenous tissue and primarily mononuclear cells. The adjacent cartilage structure was not adversely affected as observed by bronchoscopic, gross, histologic, and mechanical analysis. The W3 stents showed reproducible spatial and temporal fracture patterns, but otherwise tended to corrode quite slowly, with a mix of Ca and P rich corrosion product formed on the surface and observed focal regions of pitting. The study showed that the approach to use degradable magnesium alloys as an extraluminal tracheal stent is promising, although further development of the alloys is required to improve the resistance to stress corrosion cracking and improve the ductility. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 611–620, 2014.